Starch @ PDMS @ PU sponge for organic solvent separation. (2nd December 2022) - Li, Yushan; Li, Jie; Lu, Yiyi; Shi, Wentian; Tian, Huafeng
Abstract: Common separation materials are divided into two-dimensional (2D) materials and three-dimensional (3D) materials, among which three-dimensional materials have excellent durability and stability. Herein, we developed a durable S@P@PU sponge by simply immersing polyurethane (PU) sponges in a blending solution of starch granules and polydimethylsiloxane (PDMS). Blending starch granules and PDMS could achieve more reliable adhesion of starch granules to the PU sponge by utilizing the high adhesion of PDMS. At the same time, the presence of starch granules could make PDMS form a spot-like secondary structure on the sponge. The sponge exhibited excellent hydrophobicity and high organic solvent affinity, and could separate and absorb organic solvents from the turbulent flow. The results showed that the sponge could absorb and hold 46 times its organic solvent weight, with a separation efficiency greater than 98.5% for different organic solvents. In addition, the sponge maintained a water contact angle of more than 140° after 40 abrasion cycles or after immersion in different pH and salt solutions for 48 h, showing excellent mechanical durability and chemical stability. Graphical abstract: Image 1 Highlights: The modified sponge water contact angle is increased from 86° to 157°. In extreme environments, sponges still have water contact angles of >140°. The separation efficiency of the modified sponge is greater than 99%. The modified sponge can hold 46 times its own weight of organic solvent. The sponge has the advantages of low cost and short time consumption.